Langmuir solitons in a plasma with inhomogeneous electron temperature. (21st May 2015) - Gromov, Evgeny M; Malomed, Boris A
Abstract: Dynamics of Langmuir solitons is considered in plasmas with spatially inhomogeneous electron temperature. An underlying Zakharov-type system of two unidirectional equations for the Langmuir and ion-sound fields is reduced to an inhomogeneous nonlinear Schrödinger equation with spatial variation of the second-order dispersion and self-phase modulation coefficients, induced by a spatially inhomogeneous profile of the electron temperature. Analytical trajectories of motion of a soliton in the plasma with an electron-temperature hole, barrier, or cavity between two barriers are found, using the method of integral moments. The possibility of the soliton to pass a high-temperature barrier is shown too. Analytical results are well corroborated by numerical simulations.